Milmed Treatment Alleviated or Abolished Allergy - Archer Trevor (Journal of Immunology and Allergy, 2020)
In view of the marked levels of discomfort, pain and/or poor health induced by allergic rhinitis and related conditions, especially during seasonal proclivities, the emerging availability of novel agents, and particularly probiotics, to (a) relieve, and (b) ameliorate those expressions offers much hope to sufferers whether afflicted by seasonal or regular, chronic allergies. The patented treated-yeast, Milmed, a probiotic suspension, previously shown to possess neuroprotective and neurorestorative properties, was found to provide marked ameliorative relief against a variety of allergic reactions and asthma expressed by a moderately-sized group of twenty-one participating-patients who had reported themselves to be chronic sufferers. Following a twelve-week course of Milmed treatment, an overwhelmingly large proportion (more than 95%) of the allergy-reporting patients indicated either "moderate" or "marked improvement" or were adjudged "symptom-free". Comparisons of the patients' allergy condition from before Milmed treatment to after indicated marked and significant improvements. Notably, in view of postal service vagaries that resulted in non-deliverance of Milmed, a significant correlation between post-treatment scores and missed weeks of Milmed was obtained (r = 0.526, p < 0.014). The possibility that 10- to 12-week administrations of Milmed may offer more-or-less long-lasting relief from allergic reactions and the inclusion of Milmed among the health-enhancing list of probiotic interventions ought to be examined more closely.